The effects of dipeptidyl peptidase-4 on cardiac fibrosis in pressure overload-induced heart failure - Masanori Hirose; Hiroyuki Takano; Hiroshi Hasegawa; Hiroyuki Tadokoro; Naoko Hashimoto; Genzo Takemura; Yoshio Kobayashi (Elsevier, 2017)
Dipeptidyl peptidase-4 (DPP-4) inhibitors are hypoglycemic agents. DPP-4 inhibitor has cardioprotective effects after transverse aortic constriction (TAC), but role of DPP-4 on cardiac fibrosis after TAC is not well known. Our aim was to determine the effects of DPP-4 on cardiac fibrosis in murine TAC model. Wild-type mice and DPP-4 knockout mice were subjected to TAC. Wild-type mice were then treated with vehicle or DPP-4 inhibitor. DPP-4 activities in serum and heart tissue were significantly increased at 2 weeks after TAC, but they were significantly decreased by DPP-4 inhibitor treatment. The inhibition of DPP-4 did not affect left ventricular hypertrophy, but improved cardiac function and decreased myocardial and perivascular fibrosis after TAC. The inhibition of DPP-4 decreased the collagen type III/I ratio in myocardium. These results suggest that DPP-4 inhibition ameliorates the progression of heart failure after TAC by changing the quality and quantity of cardiac fibrosis.